Laboratory Investigation Partial Replacement of Coarse Aggregate with Coconut Shell in Concrete Mixture - Muhd Erhan, Muhammad Imran; Ahmad Khairi, Ahmad Khalis Syafif; Azmi, Amirul Ariffin; Bujang, Hazirah (Multidisciplinary Applied Research and Innovation, 2025)
The growing demand for construction materials due to population growth and urbanization has increased the cost of traditional concrete materials in Malaysia, leading researchers to explore sustainable and low-cost alternatives like coconut shells as a substitute for coarse aggregates in concrete. This study aimed to examine the effects of using coconut shells in concrete to partially replace coarse aggregates by analyzing the properties of coconut shell aggregates (CSA), measuring the compressive strength of concrete with CSA, and evaluating its effectiveness as a replacement. Coconut shells were added to concrete mixes at 0%, 5%, 10%, and 15% and tested for compressive strength according to ASTM E9-19 standards. Results showed that after 7 days, compressive strength decreased with higher percentages of coconut shells, with 0% replacement showing an average strength of 26.55 MPa and 15% replacement showing 7.20 MPa. After 14 days, 0% and 15% replacements had average strengths of 22.19 MPa and 5.00 MPa, respectively. The study concluded that using coconut shells as aggregates could reduce environmental impact and construction costs, especially in coconut farming regions where shells are abundant and inexpensive, while also evaluating the mechanical properties, workability, and durability of the concrete.